746 Single-Centre Experience with Three Metallic Ureteric Stents (Allium URS, Memokath-051 and Resonance) for Chronic Ureteric Obstruction. (12th October 2021) - Ho, C; Palaniappan, V; Ting, A; Khoo, C; Forster, L; Kondjin-Smith, M; Abboudi, H; Hanna, M; El-Husseiny, T; Dasgupta, R
Abstract: Aim: To evaluate efficacy of Allium URS, Memokath 051 and Resonance metallic ureteric stents as an alternative to polymer stents/nephrostomy in managing chronic ureteric obstruction (CUO). Method: Retrospective analysis of consecutive patients with CUO managed with Allium URS, Memokath-051 or Resonance (September 2015/July 2020). Baseline patient variables (age, gender, underlying aetiology, ASA) and stricture characteristics (length, level, continuity) were recorded. Intra- and post-operative clinical and radiological follow-up assessments at 6 weeks, 3 months and then every 6 months, as well as any emergency attendances, were reviewed for placement success, stent complications, serum creatinine, and mortality. Outcomes included placement success rate, functional stent survival, and mean renal function. Results: Overall, 129 stent insertion episodes (SIEs) (Allium URS: 23, Memokath 051: 48, Resonance: 58) occurred in 76 patients (Allium URS: 16; Memokath-051: 31; Resonance: 29). Placement success was high (Allium URS: 95.7%; Memokath-051 and Resonance: both 100%). Median functional stent survival was 11.4 months for Allium URS, 5.5 months for Memokath-051 and 11.7 months for Resonance. 47.8% of Allium URS SIEs (11/23), 64.6% of Memokath-051 SIEs (31/48) and 19% of Resonance SIEs (11/58) experienced complication (most frequently obstruction followed by migration and infection). There were no complications for Resonance SIEs for benign indication. In the first year following SIE, serum creatinine ranged from +21.3% to + 46.7% for Allium URS, -7.8% to + 8.9% for Memokath-051, and -9.4% to + 27.3% for Resonance. Conclusions: Allium URS, Memokath 051 and Resonance metallic ureteric stents are all viable management options of CUO. Resonance was particularly efficacious for patients with benign aetiology.